Design of Compact SITLs Low Pass Filter by Using Invasive Weed Optimization (IWO) Technique - Khakzad, Hamid Reza; Sedighy, Seyed Hassan; Amirhosseini, Mohammad Khalaj (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Step impedance transmission line (SITL) is optimized by Invasive Weed Optimization (IWO) technique to compact a low pass microstrip filter (LPF). In the proposed method, the uniform microstrip lines in the LPF structure are replaced by optimized SITLs. The equality of SITL and uniform transmission line gives two additional design parameters, which are optimized by IWO method to achieve the most compact SITLs. Finally, a compact high degree LPF is designed and fabricated with the area reduction of more than 70%. The measurement results of the fabricated LPF are in good agreement with the simulation ones.